2019
DOI: 10.1093/mnras/stz1172
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fractionation in external galaxies

Abstract: In star forming regions in our own Galaxy, the 14 N/ 15 N ratio is found to vary from ∼ 100 in meteorites, comets and protoplanetary disks up to ∼ 1000 in pre-stellar and star forming cores, while in external galaxies the very few single-dish large scale measurements of this ratio lead to values of 100-450. The extent of the contribution of isotopic fractionation to these variations is, to date, unknown. In this paper we present a theoretical chemical study of nitrogen fractionation in external galaxies in ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In particular, Viti et al (2011), and later Benedettini et al (2013), found that at least some of the species observed in B1 were likely the product of a non-dissociative, C-type shock with pre-shock density n(H) ≥ 10 5 cm −3 and shock velocity V s ∼ 40 km s −1 . In this section, we use their same (updated) chemical and shock time dependent gas-grain model, UCLCHEM (Holdship et al 2017), augmented with the nitrogen and carbon isotopologues chemistry (Viti et al 2019(Viti et al , 2020, to determine whether, theoretically, we should expect the passage of a shock to affect the nitrogen fractionation in L1157-B1. Full details of the chemical and shock model UCLCHEM can be found in the references above.…”
Section: Models Of Nitrogen Fractionation In Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Viti et al (2011), and later Benedettini et al (2013), found that at least some of the species observed in B1 were likely the product of a non-dissociative, C-type shock with pre-shock density n(H) ≥ 10 5 cm −3 and shock velocity V s ∼ 40 km s −1 . In this section, we use their same (updated) chemical and shock time dependent gas-grain model, UCLCHEM (Holdship et al 2017), augmented with the nitrogen and carbon isotopologues chemistry (Viti et al 2019(Viti et al , 2020, to determine whether, theoretically, we should expect the passage of a shock to affect the nitrogen fractionation in L1157-B1. Full details of the chemical and shock model UCLCHEM can be found in the references above.…”
Section: Models Of Nitrogen Fractionation In Shocksmentioning
confidence: 99%
“…In the gas phase, isotope exchange reactions at low temperatures (Roueff et al 2015) and/or isotope-selective photodissociation of N 2 (Heays et al 2014;Furuya & Aikawa 2018) seem to be the more promising processes. A recent paper by Viti et al (2019), which includes up-to-date chemical networks for 14 N and 15 N isotopic species, found that 14 N/ 15 N in HCN, HNC, and CN can vary by about an order of magnitude with time causing a possible spread in the range from ∼100 to ∼1000. In addition, an increase in the nitrogen fractionation in the ISM can be obtained in high gas densities aided by high fluxes of cosmic rays.…”
Section: Introductionmentioning
confidence: 99%
“…For the abundance ratios 12/13 C = [ 12 C]/[ 13 C], 14/15 N = [ 14 N]/[ 15 N] and 16/18 O = [ 16 O]/[ 18 O] we turn to the literature to break the degeneracy of optical depth and abundance ratio. We adopt 12/13 C = 40 ± 20 (among nearby galaxies including NGC 253, Henkel et al 2014;Martin et al 2010Martin et al , 2019Tang et al 2019), 14/15 N = 200 ± 1 dex (Viti et al 2019, and references therein, see table 1 for an overview) and 16/18 O = 130 ± 40 (NGC 253; Martin et al 2019).…”
Section: Isotopic Ratios and Optical Depthmentioning
confidence: 99%
“…The new models also rule out significant nitrogen fractionation processes in the most abundant molecules during the chemical evolution of a star-forming core. In fact, significant variations in nitrogen fractionation are theoretically predicted only in extragalactic environments strongly affected by very high fluxes of cosmic rays (Viti et al 2019).…”
Section: Introductionmentioning
confidence: 99%